Risk Factors for Anemia among Brazilian Infants from the 2006 National Demographic Health Survey - Tulio Konstantyner; Thais Cláudia Roma Oliveira; José Augusto de Aguiar Carrazedo Taddei (Anemia)
Iron deficiency is an important public health problem. An understanding of anemia risk factors is essential to informed health policies. We performed a cross-sectional study of 1,382 infants from the 2006 Brazilian National Survey on Demography and the Health of Women and Children. Mild and moderate anemia was characterised by hemoglobin levels below 11.0 and 9.5 g/dL, respectively. Rates for mild and moderate anemia were 25.9% and 9.9%, respectively. The logistic model included three risk factors for mild anemia—urban residence area (OR=2.5; 𝑃=0.004), fever in the past 2 weeks (OR=2.4; 𝑃<0.001), and age less than 12 months (OR=1.7; 𝑃=0.024). Strategies to control infant anemia should include health promotion and nutritional education for families from all socioeconomic levels. Lifestyle quality improvement based on adequate food consumption must be achieved by communities in all macroregions, and especially in urban areas.